Self-efficacy source and career adaptability: The mediating roles of career decision self-efficacy - Firosyana Rizki Amalia; Farida Kurniawati (Universitas Ahmad Dahlan, 2019)
Career adaptability is defined as individual’s ability to make self and environmental assessments in order to deal with changes that occur to themselves and the environment — both planned and unplanned. Being sure about the ability to perform tasks related career decision making is one factor that holds an important role on career adaptability. This sense of confidence is often called as career decision self-efficacy. The aim of this research was to identify which source of self-efficacy that plays a significant role to form career adaptability with career decision self-efficacy as a mediator. The study involved Year 12 grade students of senior high school, consisting of 47 male and 205 female. Career Adapt-Abilities Scale (CAAS), Career Decision-Making Self-Efficacy–Short Form (CDSE-SF), and Career Exploration and Decision Learning Experiences (CEDLE) Scale were used to collect the data. The results show that career decision self-efficacy (CSDE) mediated the relationship between each source of self efficacy to career adaptability. Four of five sources of self-efficacy provide influence through two ways, i.e. direct influence on career adaptability and through the mediating role of CDSE. Meanwhile, other people's successful experience has an influence on career adaptability only through CDSE mediation. Therefore, enhancing one or more source of self-efficacy will help adolescence develop a good career adaptability.